Management of Cerebral Herniation Secondary to Lead Encephalopathy: A Case Report - Das, Somnath; Hataway, Felicia; Boudreau, Hunter S.; Alam, Yasaman; George, Jordan A.; Rushton, William; Atti, Sukhshant; Kaur, Manmeet; Holland, Marshall T. (Frontiers in Neurology, 2022)
Background Adult lead encephalopathy is a rare but critical condition to recognize in modern healthcare settings. Few reports have described the medical and neurosurgical management of severe adult lead encephalopathy. Case Presentation A 22 year old woman presented with severe headache, anemia, vomiting, 40-lb weight loss, and constipation. At the time of presentation, she had extensive colonic radiopaque material and a serum lead concentration of 87 mcg/dl (normal <10). She rapidly developed anisocoria requiring emergent ventriculostomy insertion. Following CSF diversion, ICP mitigation, and lead chelation, she considerably improved in <2 weeks. Conclusion We report one of the few instances of successful surgical and medical management of adult lead encephalopathy. Dedicated neurocritical care and neurosurgical teams are necessary in conjunction with toxicology in order to manage the advanced sequalae of severe lead poisoning.